MENINGKATKAN PEMAHAMAN AL-QUR’AN SISWA MADRASAH IBTIDAIYAH DENGAN MENGIMPLEMENTASIKAN PEMBELAJARAN TAHFIZ BERBASIS MOTORIK - Shidqiyah; Kusnul Munfa’ati (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the relationship between motor skill completion and conceptual understanding in the Islamic Religious Education (PAI) learning process at an elementary school (Madrasah Ibtidaiyah). The research employed a qualitative approach with a case study design. Eight informants—four students and four teachers—were purposively selected based on initial findings regarding motor deficiencies through preliminary observations and the Developmental Coordination Disorder Questionnaire (DCDQ). Data collection techniques included semi-structured interviews, participant observation during Quranic recitation, memorization, and writing activities, as well as documentation studies in the form of student assignments and learning evaluation reports. Data validity was maintained through triangulation of sources, methods, and time, as well as member checking. The results showed that fine motor limitations impact the accuracy of Tajweed pronunciation, the ability to write tafsir (interpretation of the Quran), and neuromuscular coordination, ultimately affecting the tadabbur process and the devotion to learning. Meanwhile, incomplete gross motor skills cause students to easily become fatigued during group memorization activities and prayer practices, thus reducing spiritual motivation and the effectiveness of teacher role models. Data analysis using the Miles and Huberman interactive model revealed a causal relationship between motor, cognitive, and spiritual aspects in Islamic Religious Education (PAI) learning. These findings critique the view of religious education that separates the physical and spiritual dimensions and emphasize the importance of integrating motor development into memorization learning and worship practices. Research recommendations include conducting regular motor screenings, implementing therapeutic calligraphy exercises, using rhythmic prayer movements, and designing ergonomic classroom environments. This holistic approach is expected to improve overall Islamic Religious Education (PAI) understanding, support the formation of noble character, and have a lasting impact on students' lives.